The Effect of Halal Destination Image and Tourist Motivation on Revisit Intention: The Role of Halal Experience Satisfaction - Herman, Lalu Edy; Athar, Handry Sudiartha; Dakwah, Muhammad Mujahid (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Revisit intention is interesting to be studied because it relates to the behavior of tourists to revisit, particularly during the post-covid-19 pandemic that has limited tourist visits to a destination for quite a long time. Experience, in the hospitality and tourism context, is a significant concept used to understand consumer behavior. The travel experience begins before arriving at the destination, ends with memories of the experience, and plans to revisit it in the future. This study aims to investigate the effect of halal destination image and tourist motivation on the speed of deciding to revisit halal tourism destinations through halal experience satisfaction tourism destinations in Lombok Island. This study used a quantitative method with 200 domestic and foreign tourists as respondents. The results of the study showed that halal destination image and tourist motivation could not directly accelerate the tourists' decision to revisit, but they had to go through halal experience satisfaction.